[Ag(PcL)]‐Catalysed Domino Approach to 6‐Substituted Benzoxazino Isoquinolines. Issue 24 (8th June 2020) - Garanzini, Davide; Pirovano, Valentina; Menghi, Ilaria; Celentano, Giuseppe; Rizzato, Silvia; Rossi, Elisabetta; Caselli, Alessandro; Abbiati, Giorgio
Abstract : In this paper, we describe a new silver catalysed domino approach to 6‐substituted benzoxazino isoquinolines starting from 2‐alkynylbenzaldehydes and 1‐substituted‐(2‐aminophenyl)methanols. The strategy is characterized by good reaction yields, and can be performed at room temperature as well as under heating (conventional or dielectric) in different reaction times. Best results have been obtained by using silver complexes of macrocyclic pyridine‐containing ligands (PcL) as catalysts. The stereoselectivity of the transformation has been investigated by using chiral reaction partners and chiral catalysts, but unfortunately, modest stereoselectivities have been achieved. On the other hand, this approach represents an alternative synthetic strategy for the preparation of 6‐substituted benzoxazino isoquinolines, which are the key scaffold of some compounds endowed of biological activity. Abstract : 6‐Substituted benzoxazino isoquinoline nucleus, a key skeleton in some biological active molecules, can be prepared by a silver catalysed domino approach starting from 2‐alkynylbenzaldehydes and 1‐substituted (2‐aminophenyl)methanols. The silver(I) complexes of macrocyclic pyridine‐containing ligands (PcL) demonstrated to be the catalysts of choice.